Vascular access site complication in transfemoral coronary angiography between uninterrupted warfarin and heparin bridging - Wanwarang Wongcharoen (2018)
© 2017, Wiley Periodicals, Inc. Background: Warfarin discontinuation with heparin bridging is a common practice in patients receiving warfarin prior to elective coronary angiography (CAG). The uninterrupted warfarin strategy has been suggested to be alternative option for patients with high thromboembolic risk. Therefore, we aimed to assess the safety of elective transfemoral CAG during uninterrupted warfarin therapy compared to heparin bridging. Methods: This study was a randomized open-label design with blinded event evaluation. The 110 consecutive patients (age ≥ 18 years) receiving warfarin before the planned transfemoral CAG were randomly assigned to either heparin bridging or uninterrupted warfarin with targeted INR (2.0-3.0). The primary outcome was the incidence of major vascular access site complications. Results: The baseline characteristics were comparable between two groups (mean age was 60.1 ± 7.8 years, 49 males). The mean INR on the day of CAG of heparin bridging and uninterrupted warfarin groups was 1.2 ± 0.3 and 2.2 ± 0.5 (P < 0.001). The major vascular access site complications occurred in 3 of 55 (5.5%) heparin-bridging patients and in none of 55 uninterrupted warfarin patients (P = 0.243). The total vascular access site complications occurred in 6 (10.9%) heparin-bridging and one (1.8%) uninterrupted warfarin patients (P = 0.113). No patient developed either other bleeding or thromboembolic events during 7 days after CAG. Conclusions: We demonstrated that an uninterrupted warfarin strategy did not increase vascular access site complications in patients undergoing transfemoral CAG compared to heparin bridging therapy. Due to the safety and the ease of uninterrupted warfarin strategy, this approach should be encouraged in patients receiving long-term warfarin who undergo elective transfemoral CAG.